Kanabinoidi v terapiji luskavice - Prestreši, Leonora (Placebo, 2025)
Cannabinoids are compounds that influence various physiological processes in the body through the endocannabinoid system (ECS). This system plays a crucial role in regulating inflammation, immune responses, oxidative stress, and skin homeostasis. In recent years, cannabinoids have emerged as a promising topic of research, including in the treatment of psoriasis — a chronic inflammatory skin disease with a complex immunological background. Psoriasis is characterized by excessive keratinocyte proliferation, inflammation, and angiogenesis, involving numerous inflammatory cytokines and growth factors. Cannabidiol (CBD), a non-psychoactive compound derived from Cannabis sativa, has gained particular attention due to its multifaceted therapeutic potential. Studies have shown that CBD may reduce inflammation, oxidative stress, itching, and abnormal keratinocyte proliferation, while improving skin hydration. Promising results have also been observed with synthetic cannabinoids such as JWH-133, which exhibit anti-inflammatory and anti-angiogenic properties. Despite encouraging findings, further studies are necessary to confirm the efficacy and safety of cannabinoids in psoriasis treatment.
Keywords: cannabidiol; cannabinoids; CBD; endocannabinoid system; endokanabinoidni sistem; inflammation; kanabidiol; Kanabinoidi; Luskavica; psoriasis; vnetje